Effectiveness of Nepalese Online Advertisement in Recalling a Product - Vaidya, Rashesh (Journal of Nepalese Business Studies, 2022)
Online advertising is becoming more popular because it is easier to access and less expensive. Similar to this, the regulatory limitations on the use of conventional advertising instruments for advertisements in Nepal boosted the popularity of online advertisements. Therefore, a marketer also wants their advertisement to be very efficient at getting customers to remember their products. The goal of the paper is to determine how well Nepalese online advertisements help consumers recall products. The article polled 270 Nepalese customers who have gone through online advertisements. The study discovered banner ads the most preferred type of online as among the respondents. The paper found that online ads helped to make online purchasing decisions and recalling products. The respondents were concerned about the value associated with the product displayed in online ads. Similarly, the Nepalese online ad viewers did not find effective in the use of humor in online ad in recalling the products and services.